Penyelesaian Sengketa Minyak Kelapa Sawit Mentah Indonesia dengan Uni Eropa Melalui Dispute Settlement Body World Trade Organization - Meha Middlyne Simbolon; Yosef Felix Sitorus (CV Rewang Rencang, 2025)
Indonesia and the European Union are involved in an international trade dispute over palm oil, which has been addressed through the Dispute Settlement Body (DSB) of the World Trade Organization (WTO). The dispute was triggered by the European Union's policies, such as the Renewable Energy Directive II and regulations related to palm oil-based biofuel, which are considered discriminatory and detrimental to Indonesia's exports. The WTO, through the DSB, successfully mediated the trade dispute between Indonesia and the European Union. From the perspective of international law, the WTO serves as an institution that enforces binding rules, enabling it to resolve trade disputes fairly. The WTO panel reviewed the Technical Barriers to Trade Agreement and the General Agreement on Tariffs and Trade 1994, which were the core of Indonesia's objections. The panel's findings revealed that certain European Union policies violated the principle of non-discrimination, while some of Indonesia's claims were not substantiated. This article also examines the implications of the decision through the lens of the theory of comparative advantage, which supports Indonesia's right to utilize its natural advantages in efficiently producing palm oil. The WTO's decision is expected to encourage the European Union to revise its policies and strengthen Indonesia's position in global trade.